2007
DOI: 10.1253/circj.71.9
|View full text |Cite
|
Sign up to set email alerts
|

Association of Creatinine Clearance and In-Hospital Mortality in Patients With Acute Coronary Syndromes

Abstract: revious studies have demonstrated that renal insufficiency is an independent risk factor for cardiovascular morbidity and for all-cause as well as cardiovascular death in both the general population and patients with cardiovascular disease. [1][2][3][4] In particular, recent studies have shown that any stage of renal dysfunction (mild to severe) is an independent risk factor for short-and long-term mortality among patients with myocardial infarction (MI), even after administration of fibrinolytics. [5][6][7][8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 24 publications
2
27
0
3
Order By: Relevance
“…In the present study, renal insufficiency was significantly correlated with Killip class ≥II (p=0.026). In addition, renal function decreases with age, 9 and in the present study age was identified by univariate analysis as a predictor of painless MI. However, multivariate analysis of the factors identified with univariate analysis, including age and Killip class ≥II, showed that only renal insufficiency was an independent predictor for painless MI (Table 4).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In the present study, renal insufficiency was significantly correlated with Killip class ≥II (p=0.026). In addition, renal function decreases with age, 9 and in the present study age was identified by univariate analysis as a predictor of painless MI. However, multivariate analysis of the factors identified with univariate analysis, including age and Killip class ≥II, showed that only renal insufficiency was an independent predictor for painless MI (Table 4).…”
Section: Discussionsupporting
confidence: 60%
“…However, multivariate analysis of the factors identified with univariate analysis, including age and Killip class ≥II, showed that only renal insufficiency was an independent predictor for painless MI (Table 4). A recent study has shown that time from symptom onset to admission is longer in patients with renal insufficiency, 9 possibly because of a lack of painful symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated in a study made by Komukai et al that as the renal function disorders increased, the prevalence of painless MI also increased (Komukai et al, 2007). In another study conducted by Pitsavos C et al, it was shown that MI patients with renal failure admitted to the hospital late and the possible reason for such late admission was thought to be the less occurence of alerting symptoms such as chest pain in this patient group (Pitsavos et al, 2007). Late admissions certainly mean that coronary interventions are less and mortality is more.…”
Section: Myocardiac Infarctionmentioning
confidence: 88%
“…Renal function per se did not influence the anticoagulation activity of UFH (Fig 5). The reported higher [18][19][20] risk of bleeding in patients with renal dysfunction treated with UFH is a consequence of the complex impairment of coagulation in those patients. 21 In accordance with this, we found a correlation between the level of serum creatinine and loss of hemoglobin (Fig 5).…”
Section: Discussionmentioning
confidence: 99%